EFEKTIVITAS STRATEGI INOVASI DAN KREATIVITAS USAHA TERHADAP RESILIENSI UMKM ABON DI KABUPATEN CIANJUR - Nabila Ramadani; Tetty Sufianty Zafar; Sopyan Saori (Journal of Economic, Bussines and Accounting (COSTING), 2026)
MSMEs play a vital role in supporting the regional and national economies; however, various post-disaster challenges and changes in the business environment have resulted in relatively low resilience among some MSMEs. This study aims to analyze the influence of innovation strategies and business creativity on the resilience of Abon SMEs in Cianjur Regency. The study employs a quantitative approach using descriptive and associative methods. The sample consists of 34 SME operators selected using a saturation sampling technique. Data collection was conducted through the distribution of questionnaires. The results indicate that innovation strategies have a positive and significant effect on SME resilience. Business creativity also has a positive and significant effect on resilience and is the most dominant variable in enhancing SMEs’ ability to survive and adapt. Simultaneously, innovation strategies and business creativity have a significant effect on SME resilience with a very strong correlation. These findings indicate that the ability to develop product, process, and marketing innovations—supported by creativity in generating new ideas and solutions—can enhance business resilience in the face of market changes, competition, and crisis conditions. This study concludes that innovation strategies and business creativity are critical factors in strengthening the resilience of Abon SMEs in Cianjur Regency. Therefore, MSME operators are advised to continue fostering innovation and creativity through the use of digital technology, product development, and improved adaptability to ensure the long-term sustainability of their businesses.